Dental fear and anxiety among children and their caregivers - Gerhardt de Oliveira, Marília; Ávila, Roberta Alencastro; Carvalho e Silva, Roberta Rossi; Gomes, Fernando Vacilotto; de Moraes, João Feliz Duarte; Weber, João Batista Blessmann (Revista de Ciências Médicas e Biológicas, 2015)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false PT-BR JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria; –> <!–[endif] –> <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Introduction: Dental treatment is an experience that elicits fear and anxiety in most people, and particularly in children. This fear is the first step to be overcome in the search for a satisfactory dentist-patient relationship. Aim: of this research was to assess fear and anxiety among children and their caregivers when faced with dental treatment and identify the main reasons behind these behaviors. Methodology: About 200 questionnaires consisting of nine multiple-choice questions and one open-ended question, to obtain additional information, were administered to male and female patients aged 4 to 13 years who were treated at a university pediatric dentistry clinic and to their respective caregivers. Results: show only one-third of children reported fear of the dentist. Pain, needles, and anesthesia were the main reasons behind their feelings of fear. Over 70% of interviewed children reported having experienced tooth pain at least once, which reinforces the importance of painful experiences as being associated with dental fear in a portion of these patients. Conclusion: that although dental fear was uncommon among caregivers, approximately one-third of children reported fear of the dentist, associated with perceived pain or needle phobia. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–EndFragment–>